2021
DOI: 10.3329/aajbb.v6i1.54879
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility patterns of Vibrio cholerae in dairy excreta

Abstract: Vibrio cholerae is a major etiological agent of human diarrhoea and has become epidemic across the world in the recent past. A cross-sectional study was conducted to assess the prevalence of V. cholerae from dairy excreta along with antimicrobial resistant status of the isolates. A total 50 samples were collected from 50 different household manure pit located at Bangladesh Agriculture University (BAU) surrounding area, Mymensingh. Alkaline peptone water was used for enrichment of the samples followed by inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Studies confirm that cross-reactions of Vibrio cholerae with other pathogens (Brucella spp., Escherichia coli, or Escherichia hermannii) should also be taken into account when assessing seropositivity [31]. A study published in 2021 showed the presence of Vibrio cholerae in as many as 34% of fecal samples collected from dairy cows [32]. Some other studies report the presence of Vibrio spp.…”
Section: Cattlementioning
confidence: 99%
“…Studies confirm that cross-reactions of Vibrio cholerae with other pathogens (Brucella spp., Escherichia coli, or Escherichia hermannii) should also be taken into account when assessing seropositivity [31]. A study published in 2021 showed the presence of Vibrio cholerae in as many as 34% of fecal samples collected from dairy cows [32]. Some other studies report the presence of Vibrio spp.…”
Section: Cattlementioning
confidence: 99%
“…The improper antimicrobial drug used for humans is diffusive in developing countries and is a significant contributor to growing the public health threat of AMR-resistant bacteria (Roess et al, 2013). In recent years, the indiscriminate use of antibiotics in animals and poultry is thought to be an important factor to develop of AMR Al-Salauddin et al, 2015;Sohidullah et al, 2016;Rahman et al, 2016;Talukder and Ahmed, 2016;Roy et al, 2017;Jahan et al, 2017;Kabir et al, 2018a;Kabir et al, 2018b;Kamal et al, 2018;Alam et al, 2019;Rumi et al, 2019;Saif et al, 2019;Masud et al, 2020;Alam et al, 2020;Sarker et al, 2020;Mridha et al, 2020;Matubber et al, 2021;Uddin et al, 2021;Tresha et al, 2021;Eashmen et al, 2021;Haque et al, 2021;Hosain et al, 2021;Arif et al, 2022;Hoque et al, 2022). In Bangladesh, the most common reason for choosing an antimicrobial is personal experience and perception (68%), rather than the cultural sensitivity test which may be due to a lack of vet diagnostic facilities and the unwillingness of the veterinary personnel (Pokharel et al, 2020).…”
Section: Development Of Antimicrobial Resistance (Amr)mentioning
confidence: 99%
“…For example, Salmonella spp. an MDR (Multi Drug Resistant) zoonotic microorganism that can spread from animals to humans, was identified as resistant to several antibiotics due to certain resistant genes, named as 'tetA' and 'SHV', including erythromycin (87.5%), tetracycline (86.76%), oxytetracycline (75.73%), and so forth ( Eashmen et al, 2021;Sobur et al, 2019;Kabir et al, 2018;Hasan et al, 2018;Hossain et al, 2017). The farmers who work closely with livestock have high chances of acquiring the AR microbes, which can put both animal and public health at risk.…”
Section: Introductionmentioning
confidence: 99%